2001
DOI: 10.1007/bf03395408
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Ordinal Position Information with Limited and Extended Serial Training

Abstract: To examine the possibility that position cues are temporal and therefore ineffective early in serial runway training, rats were runway trained on a three-trial series of different rewards. The series was SNP', where Sand P' refer to series trials that concluded with four sucrose or eight plain Noyes pellets, respectively. The middle trial was never rewarded (N) . Early in training, a significant pattern of running slowly on the middle trial and rapidly on the initial and terminal trials had emerged. Transfer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…One possibility entertained by Capaldi et al (1997) was that position learning requires extensive training, but reward-memory learning occurs rapidly. However, Burns and Criddle (2001) found that slower running on the middle trial of an SNP series appeared also on the middle trial of an NNN transfer series after both limited and extensive training.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…One possibility entertained by Capaldi et al (1997) was that position learning requires extensive training, but reward-memory learning occurs rapidly. However, Burns and Criddle (2001) found that slower running on the middle trial of an SNP series appeared also on the middle trial of an NNN transfer series after both limited and extensive training.…”
Section: Discussionmentioning
confidence: 96%
“…New experiments examining the duration of training in Phase 2 using this procedure would be informative, but the data from Burns and Criddle (2001) suggest that the overshadowing of memory cues occurs quite early.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations